The Effect Of Gymnastics In The Elderly To The Elderly Blood Pressure With Hypertension In Ederly Gymnastic Group In Banjar Kaja Sesetan Denpasar Selatan - Putu Dyah Astari (Coping: Community of Publishing in Nursing, 2013)
Hypertension is a common disease in the elderly. Hypertension is also a risk factor for cardiovascular disease. High incidence of hypertension in the elderly requires health professionals to perform the role of prevention and health promotion efforts. The prevention can be done to prevent the hypertensive elderly by doing non-pharmacological therapies are breathing exercises and gymnastics in the elderly. This study aims to determine the effect of breathing exercises and gymnastics in the elderly on blood pressure elderly with the hypertension.This study is a Pre-Eksperimental with used a design One Group Pre Test-Post test Design. This study is a technique purposive sampling and obtained 24 people samples in 55 people population, which selected according to the inclution criteria. The research was conducted in Banjar Kaja Sesetan for 2 weeks in different days they are Sunday, Tuesday and Friday.The results of the analysis using non-parametric test Wilcoxon test showed that breathing exercises and gymnastics in the elderly affects the elderly with hypertension, blood pressure (p < 0,05).According on the finding result of the study suggested to the Banjar Kaja Sesetan to always give breathing exercises and gymnastics in the elderly three times a week.